المصطلح النقدي في الخطاب السردي العراقي : مرحلة الريادة أنموذجا - حمادي، صبري مسلم (جامعة القادسية - كلية التربية, 2010)
The present study deal's with the critical idiom in Iraqi narrative discourse, during the formative years. Establishing a rework of critical idiom and identifying their designation so as to reach a general consensus a bout them is the first step in any scholarly critical work. An important issue her is how to achier a match in the Iraqi critical idiom between the linguistic history the Arabic word and its connotation in the original foreign idiom
755388
Keywords: القصة القصيرة -- العراق -- الخطاب السردي -- المصطلح النقدي -- الادب العربي -- النقد الادبي